Emergence and characterization of a ST852 Klebsiella quasipneumoniae clinical isolate coharboring blaNDM-1 and blaKPC-2 in China - Tian, Chongmei; Zhao, Yaping; Dong, Su; You, Zhixin; Chen, Jingbai; Xu, Hongfeng; Fang, Yuejuan; Zhang, Yapei (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesTo characterize a rare ST852 Klebsiella quasipneumoniae strain co-producing NDM-1 and KPC-2 isolated from a clinical patient.MethodsMinimum inhibitory concentrations (MICs) were measured using a VITEK 2 compact system and broth microdilution. Conjugation experiments were conducted using film matings. Whole genome sequencing (WGS) was performed using Illumina and Nanopore platforms. Antimicrobial resistance determinants were identified using the ABRicate program in the ResFinder database. Insertion sequences (ISs) were identified using ISFinder. Bacterial virulence factors were identified using a virulence factor database (VFDB). Genome function annotation and classification were further analyzed using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Cluster of Orthologous Groups (COG) databases. Capsular polysaccharides (KL) and lipooligosaccharides (OCL) were tested using Kleborate with the Kaptive. Multilocus sequence typing (MLST) and replicon types were identified using the Center for Genomic Epidemiology website. Prophage region analysis was performed using PHASTEST software. Conjugation-related elements were predicted using oriTfinder. The plasmid structure was visualized using Circos and similar plasmids in the public database were tracked using BacWGSTdb. A global phylogeny for the ST852 K. quasipneumoniae isolates was further performed.ResultsK. quasipneumoniae KPSY isolate was identified as ST852, with KL18 and O3/O3a. It has an extensive drug-resistant (XDR) profile. WGS analysis revealed that it contained one circular chromosome and three plasmids. The results of the COG and KEGG functional classifications showed that most of the functions were associated with metabolism. pKPSY-2 is a 239,226-bp IncU plasmid carrying the carbapenem resistance gene blaNDM-1. pKPSY-3 is a smaller plasmid belonging to the IncN-type conjugative plasmid with blaKPC-2. Importantly, oriT sequence, the T4SS region, T4CP, and relaxase were identified. Tracking of the blaKPC-2 plasmids showed they were identified in different species in different countries, including E. coli, Leclercia sp., Pantoea sp., and E. hormaechei. Global analysis data showed 13 ST852 strains were mainly isolated from China (84.62%, 11/13), and the remaining isolates were collected from Switzerland.ConclusionsThis is the first study to identify an ST852 NDM-1-KPC-2 coproducing K. quasipneumoniae clinical isolate. Surveillance is warranted, and early detection of this high-risk clone in the clinic is recommended to avoid its extensive spread.